CM 2022
DOI: 10.18137/cardiometry.2022.22.5055
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of mitochondrial therapy: preventing development of myocardial infarction and blocking metastatic aggression of B16/F10 melanoma

Abstract: The aim is to evaluate the physiological parameters of the efficacy of cardiac mitochondria transplantation in male mice with chronic neurogenic pain and B16/F10 melanoma growth. Materials and methods. Male mice (n=37) of the C57BL/6 line were used in the research work. The animals covered experimental groups as follows: mice with chronic neurogenic pain (CNP) + B16/F10 melanoma (n=27); mice with CNB + B16/ F10 melanoma + mitochondrial therapy (MC therapy) (n=10). Mitochondria were isolated from the heart of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…So, in some experiments on mice it has been established that therapy of malignant tumors with the use of mitochondria isolated from the liver inhibits the tumor growth due to reduction in glycolysis and oxidative stress [4]. Besides in our previous research works we have demonstrated a successful application of metabolically active mitochondria to produce an effect of suppression of the primary tumor focus of melanoma with blocking metastazing; we have also presented the respective morphological substantiation of the mechanism of this sort of actions in experimental animals [5,6]. In some other experimental studies, upon determination of the dysfunction of mitochondria in cardiomyocytes against the background of chronic neurogenic pain, followed by transplantation of metabolically active mitochondria of the heart, elimination of the occurrence of myocardial infarction events has been shown [7,8,9].…”
Section: Introductionmentioning
confidence: 76%
“…So, in some experiments on mice it has been established that therapy of malignant tumors with the use of mitochondria isolated from the liver inhibits the tumor growth due to reduction in glycolysis and oxidative stress [4]. Besides in our previous research works we have demonstrated a successful application of metabolically active mitochondria to produce an effect of suppression of the primary tumor focus of melanoma with blocking metastazing; we have also presented the respective morphological substantiation of the mechanism of this sort of actions in experimental animals [5,6]. In some other experimental studies, upon determination of the dysfunction of mitochondria in cardiomyocytes against the background of chronic neurogenic pain, followed by transplantation of metabolically active mitochondria of the heart, elimination of the occurrence of myocardial infarction events has been shown [7,8,9].…”
Section: Introductionmentioning
confidence: 76%
“…The result of repeated intraperitoneal infusion of a suspension of living mitochondria was not only the prevention of myocardial infarction, but also the blocking of the metastatic aggression of B16/F10 melanoma, growing against the background of chronic neurogenic pain. Complete blocking of metastatic lesions of internal organs was revealed in animals with mitochondrial therapy, while in animals of the reference group, metastases in the lungs were observed in 100% of the cases, and in the spleen -in 95% of the cases, respectively [52,53]. To explore the mechanisms of influence produced by mitochondrial therapy, the content of factors, which induce apoptosis, free radical oxidation, the self-organization processes in the mitochondria of the heart and other somatic organs (brain, liver, skin, tumors) during the growth of melanoma B16 and CNP was investigated.…”
Section: Pulses Of Extra-depolarization Of Switching-off Programmentioning
confidence: 91%
“…However, in recent years, the mitochondrial dynamics and its impact on bio-energetics and cellular homeostasis have also come to be appreciated. Mitochondria undergo their regular cycles of fusion and fission, regulated by various signals, including the energy needs of the cell and pathophysiological stimuli, and there is a network of critical proteins and membrane lipids involved in mitochondrial dynamics found there [22][23][24][25]. Hepatocytes are highly active metabolic cells, which have a large number of mitochondria, suggesting a biologically significant role for mitochondrial dynamics in hepatocyte damage and repair.…”
Section: Introductionmentioning
confidence: 99%